Emotion in the library workplace - Hines, Samantha; Matteson, Miriam L. (Emerald Publishing Limited, 2017)
Emotions are prevalent in the library workplace leading to many questions and areas of analysis worth exploring. For example, what tools for developing emotional intelligence are used effectively in library workplaces? How can emotional labor be managed to minimize the negative effects of emotion work? How can library employees express authentic emotions while still adhering to service expectations? How does dispositional affect how one experiences emotions - influence relationships in the workplace? What role does emotion play in effective as well as ideal library leadership and management? In this volume, we consider how emotions or related concepts such as affect, mood, or discrete feelings intersect with library administration. Offering eleven chapters ranging through inward reflection to outward practice, fourteen authors explore how theory has been applied in the study of emotion in the library workplace and provide a look at future trends in the area. Library managers will take away increased knowledge about how the library workplace can and should operate with consideration toward emotion, and will glean ideas for implementation with their own staff and services.
Includes index.
Keywords: Library administration.; Emotions -- Sociological aspects.; Psychology, Emotions.; Psychology: emotions.; elektronické knihy; electronic books